Realisasi Proses Transitivitas pada Pidato Shinzou Abe di Acara “Singapore Lecture” ke-33 - Mu'alim Nur Ahsan; Eri Kurniawan; Retty Isnendes (Departement of Mathematics Education, 2024)
This research discusses how the transitivity process was realized in Shinzou Abe's speech at the 33rd